Gambaran Pengetahuan Ibu Mengenai Status Gizi Balita di Desa Telaga Sari Tahun 2024 - Adriana Bangun; Adelina Fitri Tanjung; Putri Nadila; Revina Untari; Miftah Hul Husna Hutagalung; Dea Novita Sari (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2025)
Nutritional status is a measure of success in fulfilling nutritional needs in children which is shown through the achievement of body weight for age. The nutritional status of toddlers is very significant as a starting point for physical capacity in adulthood. This descriptive study uses primary data, namely data obtained from direct field observations using a questionnaire that has been designed previously to determine maternal knowledge about nutritional status in toddlers in Telaga Sari Village, Sunggal District, Deli Serdang Regency, as many as 30 people in this study. Based on research from 30 people who became respondents, the Description of Mother's Knowledge about nutritional status in toddlers in Telaga Sari Village, Sunggal District, Deli Serdang Regency, the majority of 14 people (47%) have sufficient knowledge and a minority of 6 mothers who have less knowledge (20%). Based on age, the majority were 20-35 years old (23%), and the minority were 1 person (3%) aged <20 years old. Based on education, the majority were high school (27%), and the minority were elementary school (3%). Based on occupation, the majority were employed (27%), and the minority were unemployed (7%). This study is expected to encourage village midwives to provide more information through counseling and increase mothers' knowledge about the nutritional status of toddlers to prevent malnutrition.